Microbiological analysis of red meat, poultry and eggs - Mead, G. C. (Geoffrey Charles), 1934- (Cambridge : Woodhead, 2007)
Red meat, poultry and eggs are, or have been, major global causes of foodborne disease in humans and are also prone to microbiological growth and spoilage. Consequently, monitoring the safety and quality of these products remains a primary concern. Microbiological analysis is an established tool in controlling the safety and quality of foods. Recent advances in preventative and risk-based approaches to food safety control have reinforced the role of microbiological testing of foods in food safety management. In a series of chapters written by international experts, the key aspects of microbiological analysis, such as sampling methods, use of faecal indicators, current approaches to testing of foods, detection and enumeration of pathogens and microbial identification techniques, are described and discussed. Attention is also given to the validation of analytical methods and Quality Assurance in the laboratory. Because of their present importance to the food industry, additional chapters on current and developing legislation in the European Union and the significance of Escherichia coli 0157 and other VTEC are included. Written by a team of international experts, "Microbiological Analysis of Red Meat, Poultry and Eggs" is certain to become a standard reference in the important area of food microbiology.
Keywords: Dierlijke voedingsmiddelen; Voedselveiligheid